2008
DOI: 10.1213/ane.0b013e31816f2616
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nicotine for Analgesia After Radical Retropubic Prostatectomy

Abstract: The preoperative application of a 7 mg nicotine patch resulted in a significant reduction in opioid consumption in patients undergoing RRP under general anesthesia. Despite this reduction in opioid use, there was no reduction in pain scores or postoperative nausea and vomiting with the use of transdermal nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 31 publications
4
23
1
1
Order By: Relevance
“…These results are in agreement with the findings of Habib et al who found that patients underwent radical retropubic prostatectomy and were treated with preoperative TDN patch 7 mg showed significantly lower cumulative morphine consumption at 24 h [28]. Our results were also supported with the study by Ahmed Nagy and ElKadi who demonstrated that using TDN patch (5 mg/16 h) as an analgesic modality adjunctive to thoracic epidural analgesia (TEA) for patients undergoing thoracotomy was accompanied by significantly lower VAS scores and significantly lower consumption of rescue analgesia in patients who received nicotine patch compared with those who received placebo [33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with the findings of Habib et al who found that patients underwent radical retropubic prostatectomy and were treated with preoperative TDN patch 7 mg showed significantly lower cumulative morphine consumption at 24 h [28]. Our results were also supported with the study by Ahmed Nagy and ElKadi who demonstrated that using TDN patch (5 mg/16 h) as an analgesic modality adjunctive to thoracic epidural analgesia (TEA) for patients undergoing thoracotomy was accompanied by significantly lower VAS scores and significantly lower consumption of rescue analgesia in patients who received nicotine patch compared with those who received placebo [33].…”
Section: Discussionsupporting
confidence: 93%
“…Although nicotine has the potential to increase heart rate and blood pressure because it activates autonomic as well as central cholinergic receptors [39], the current study did not show any significant difference in postoperative heart rate or blood pressure measurements with transdermal nicotine application versus placebo treatments. These results coincide with previous studies by Flood and Daniel; Habib et al; Hong et al; Turan et al and Ali and Sakr in which the authors hypothesized that autonomic stimulation may have been offset by the fact that patients treated with nicotine were in less pain than those treated with placebo [41,28,42,43,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…123 In males undergoing radical retropubic prostatectomy, nonsmokers who received a 7 mg/24 h transdermal nicotine patch applied before general anesthesia significantly reduced morphine requirements in the first 24 h postoperatively. 124 In contrast, Turan et al reported that 21 mg/24 h transdermal nicotine patches did not improve postoperative pain or have opioid-sparing effects in females undergoing abdominal hysterectomy. 125 However, 61% of the subjects in this study were smokers and thus chronically exposed to nicotine.…”
Section: Human Studiesmentioning
confidence: 95%
“…Available studies indicate that intraoperative nicotine does not produce marked hemodynamic changes, 123 but it may be associated with increased postoperative nausea, 124 a well known effect in nicotine-naïve subjects. 127 Many, but not all, studies find a positive association between smoking and low back pain, with the results from studies with larger samples being more likely to reach statistical significance.…”
Section: Human Studiesmentioning
confidence: 99%